(untitled) (Shanti Journal, 2023)
This research aimed to analyze Baasan’s psychological stability, the main character of the novel “Green Eyed Lama’’ by Oyungerel Tsedevdamba as depicted in the true story of repression during 1937-1947 in Mongolia. In conducting this research, the researchers apply mixed methods including qualitative descriptive and quantitative data analysis. The researchers use documentation to collect 49 examples which expressed the main character’s conscious and subconscious actions from the novel. Then a questionnaire for 42 informants was conducted and the author’s speech about the novel was used as the technique for verifying the validity and reliability of the research. Research results were analyzed through classification and triangulation methods in the sense of contextual validity data and focusing on what psychological changes the main character has based on the Theory of Individual Psychology by Alfred Adler. The research result was concluded by focusing on the following three main points. Firstly, the main character’s psychological balance was portrayed in relation to social phenomena. Secondly, the main character’s subconscious feelings such as enjoyments, dreams, love, frustrations and fears were described by metaphoric language including idioms, and comparisons in various scenes to help achieve in-depth thinking and nature to make the novel more artistic. Finally, the psychological implications of the main character were attracted to the public which made the novel to be awarded as the Best Seller.